Cytokine Levels in the Serum of Healthy Subjects - Giulio Kleiner; Annalisa Marcuzzi; Valentina Zanin; Lorenzo Monasta; Giorgio Zauli (Mediators of Inflammation)
Growing knowledge about the cytokine network response has led to a better comprehension of mechanisms of pathologies and to the development of new treatments with biological drugs, able to block specific molecules of the immune response. Indeed, when the cytokine production is deregulated, diseases often occur. The understanding of the physiological mechanism of the cytokine network would be useful to better comprehend pathological conditions. Moreover, since the immune system and response change their properties with development, differences in patients' age should be taken into account, both in physiological and in pathological conditions. In this study, we analyzed the profile of 48 cytokines and chemokines in the serum of healthy subjects, comparing adults (≥18 years) with young children and children (1–6 and 7–17 years). We found that a certain number of cytokines were not being produced in healthy subjects; others showed a constant serum level amongst the groups. Certain cytokines exhibited a downward or an upward trend with increasing age. The remaining cytokines were up- or downregulated in the group of the children with respect to the other groups. In conclusion, we drew some kinds of guidelines about the physiological production of cytokines and chemokines, underling the difference caused by aging.